Colony Cage Systems with Tunnel Ventilation and Automatic Feeding: A Review of Innovations and Their Effects on Productivity and Health of Laying Hens - Mangngi, Frans; Y.I. Sakan, Gerson; Hanmina, Marsianus Mario Fredirikus; Pono, Viky George Lettu Radja; Amnifu, Lodia Semaya; Nafi, Sulche Ifone (Universitas Syiah Kuala, 2025)
The poultry industry has experienced significant transformation driven by innovations in housing systems aimed at improving productivity and animal welfare. This study focuses on the integration of colony cage systems with tunnel ventilation and automatic feeding technologies as a comprehensive approach to optimize laying hen performance. The objective is to review existing literature to assess the impacts of these innovations on productivity indicatorssuch as egg production rate, feed conversion ratio, and resource efficiencyand on health outcomes including stress markers, plumage condition, and mortality rates. A qualitative literature review method was applied, synthesizing data from peer-reviewed journals, conference proceedings, and credible academic sources published between 2020 and 2025. Content analysis was employed to categorize findings into themes of productivity, health, feed efficiency, and welfare. Results indicate that colony cage systems enriched with perches and nesting areas allow hens to perform natural behaviors while maintaining production efficiency. Tunnel ventilation contributes to environmental stability, reducing heat stress and supporting consistent feed intake, whereas automatic feeding systems minimize feed wastage, ensure precise ration delivery, and lower stress associated with competition. When integrated, these technologies synergistically improve egg production rates, enhance feed efficiency, reduce stress markers, and decrease mortality. Nevertheless, outcomes remain highly dependent on system design, strain adaptation, and management practices. Overall, integrated colony cage systems with tunnel ventilation and automated feeding offer a promising direction for sustainable and welfare-oriented poultry farming.